Technology and organization essays in honour of Joan Woodward - Phillips, Nelson; Griffiths, Dorothy S.; Sewell, Graham (Bingley, UK : Emerald Group, 2010)
It is now 35 years since the death of Professor Joan Woodward, one of the founding figures of organization studies. Professor Woodward died in 1971 at the age of 54 after a relatively brief but highly distinguished career as a management researcher and teacher, and just six years after the publication of her landmark book Industrial Organization. At the time of her death, Professor Woodward was the Chair in Industrial Sociology at Imperial College London, having been elected as only the second women professor at the College in 1970. She joined the Production Engineering and Management Section of Imperial in 1958 and the majority of her most important work was published during this period. Prior to this she had spent a number of years at the South East Essex College of Technology where she conducted much of the empirical work that informed her significant contributions to the field.
Preface / Nelson Phillips, Graham Sewell, Dot Griffiths -- Introduction: Joan Woodward and the study of organizations / Graham Sewell, Nelson Phillips -- Joan Woodward: a personal memory / Dorothy Griffiths -- From medieval history to smashing the medieval account of organizations / Charles Perrow -- Joan Woodward: a style fit for the task / Sandra Dawson -- Working with Joan Woodward / Lisl Klein -- The contribution of Joan Woodward: a personal reflection / C.R. (Bob) Hinings -- We are what we do (and how we do it): organizational technologies and the construction of organizational identity / Davide Ravasi and Anna Canato -- Letting users into our world: some organizational implications of user-generated content / Shahzad Ansari and Kamal Munir -- Entrepreneurship and the construction of value in biotechnology / Sarah Kaplan and Fiona Murray -- Institutional sources of technological knowledge: a community perspective on nanotechnology emergence / Tyler Wry, Royston Greenwood, P. Devereaux Jennings and Michael Lounsbury -- Project-based innovation: the world after Woodward / Andrew Davies and Lars Frederiksen -- Taking time to understand: articulating relationships between technologies and organizations / Jennifer Whyte -- Technology and organization: contingency all the way down / Wanda J. Orlikowski and Cynthia Hardy -- Textualizing technology: knowledge, artifact, and practice / Cynthia Hardy -- Technology, institutions, and entropy: understanding the critical and creative role of maintenance work / Graham Dover, Thomas B. Lawrence -- What are business models? Developing a theory of performative representations / Markus Perkmann, André Spicer -- The role of structured intuition and entrepreneurial opportunities / Gerard George, Adam J. Bock -- The organization of technological platforms / Annabelle Gawer.
Description based on print version record.
Includes bibliographical references.
Print version record
Keywords: Woodward, Joan, -- 1916-1971.; Organizational behavior; Industrial organization; Industrial organization -- Technological innovations; Organizational theory & behaviour; History of engineering & technology; Business & Economics -- Organizational Behavior; Technology & Engineering -- History; Technology & Engineering -- General